Spirometry, cardiopulmonary exercise testing and the six-minute walk test results in sarcoidosis patients - Kiani, Arda; Eslaminejad, Alireza; Shafeipour, Mohsen; Razavi, Fatemeh; Seyyedi, Seyyed Reza; Sharif-Kashani, Babak; Emami, Habib; Bakhshayesh-Karam, Mehrdad; Abedini, Atefeh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: The 6-minute walking test, cardiopulmonary exercise testing, and spirometry are useful tools for evaluation of respiratory impairment and functional capacity in patients with lung disease. Sarcoidosis is a multisystem granulomatous disease of unknown etiology. Objectives: Since the pulmonary involvement can affect the quality of life in sarcoidosis patients, this study is aimed to evaluate the tests mentioned above in order to examine the functional capacity of sarcoidosis patients in different stages as well as the cause of exercise intolerance. Methods: This cross-sectional study was carried out on 50 Iranian patients with sarcoidosis. Patients were classified into three groups based on the findings of the chest radiography as well as the pulmonary CT scan, reported by an expert radiologist. Pulmonary, cardiac, and activity function have been evaluated in the patients, using cardiopulmonary exercise testing, the 6-minutes walking test, and spirometry. Results: In cardiopulmonary exercise testing, percent-predicted peak VO2 (57.75±15.49, p=0.015) and percent-predicted O2 pulse (70.54±17.37, p=0.013) were significantly lower in the third group, in comparison with the others. Also, VE/CO2 (AT) (34.99±5.67, p=0.000) was significantly higher in the third group, in comparison with the other ones. Percent-predicted VO2 showed a strong positive correlation with age (r=0.377, p=0.009), TSH (r= 0.404, p=0.007), and percent-predicted FVC (r=0.443, p=0.002). In addition, O2 pulse had a positive correlation with BMI (r=0.324, p=0.026), percent-predicted FVC (r=0.557, p= 0.000), and percent-predicted FEV1 (r=0.316, p=0.032). Conclusions: According to this study, ventilatory limitation, pulmonary involvement, and deconditioning are the main causes of activity limitations in sarcoidosis patients.